MIND diet score and its association with metabolic dysfunction-associated steatotic liver disease and gut microbiota profiles: a cross-sectional study - Yang, Shengbo; Zhang, Litao; Hu, Mingli; He, Weina (Frontiers in Nutrition, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD) is a rising health issue linked to poor diet and gut microbiota dysbiosis. The Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet, high in polyphenols and anti-inflammatory nutrients, may help protect against MASLD. This study examined how adherence to the MIND diet relates to MASLD severity, focusing on hepatic steatosis, fibrosis, insulin resistance, inflammation, and gut microbiota diversity.MethodsA cross-sectional analysis of 450 adults with confirmed MASLD was conducted. MIND diet scores were derived from a validated FFQ. Hepatic outcomes were assessed via ultrasonography, hepatic steatosis index (HSI), controlled attenuation parameter (CAP), and fibrosis-4 (FIB-4) index. Biomarkers included liver enzymes (ALT, AST, GGT, and ALP), HOMA-IR, lipid profile, C-reactive protein (CRP), lipopolysaccharide (LPS), and trimethylamine N-oxide (TMAO). Gut microbiota composition was analyzed using 16S rRNA sequencing.ResultsHigher MIND scores were associated with reduced steatosis as measured by HSI and CAP, lower fibrosis indicated by the FIB-4 index, improved insulin sensitivity reflected by lower HOMA-IR values, decreased liver enzyme levels, and a more favorable lipid profile. Inflammatory markers (CRP, LPS) decreased with higher adherence (all p < 0.001). Each 1-unit increase in MIND diet score was significantly associated with reductions in fasting insulin (β = −0.20 μU/mL; p < 0.001), HOMA-IR (β = −2.11; p < 0.001), CRP (β = −2.12; p < 0.001), LPS (β = −8.52; p < 0.001). Notably, Simpson diversity index scores were higher, and the Firmicutes-to-Bacteroidetes ratio (F/B ratio) was lower, among participants with greater MIND adherence, reflecting improved microbial balance. Mediation analysis revealed that Simpson diversity partially mediated the relationship between MIND score and liver health indicators, suggesting a role for gut microbial diversity in modulating hepatic outcomes.ConclusionGreater adherence to the MIND diet was associated with indicators of better liver function, lower systemic inflammation, and improved metabolic health, and a more favorable gut microbiota composition in adults with MASLD.